Educational failure, unsuccessful education in Mexico? - Lara González, José David (Nómadas. Critical Journal of Social and Juridical Science, 2013)
This essay performs a brief historical tour of the evolution of education in Mexico with an emphasis on higher education. It raises the conditions under which functioned education and brings its extensive problems and limitations. By means of a qualitative study and not quantitative noted the current circumstances and considered that the main cause of the educational and social crisis in the country is due to the neoliberal model. It shows the prevailing contradictions and ends assuming that there is not an educational failure nor education is unsuccessful in Mexico.
Keywords: history; education system; neo-liberalism; teaching staff; sustainability